Taxonomic revision of the flea genus AgastopsyllaJordan & Rothschild 1923 (Siphonaptera: Ctenophthalmidae) - MARIA FERNANDA LÓPEZ-BERRIZBEITIA; JULIANA SANCHEZ; RUBEN MARCOS BARQUEZ; MÓNICA DÍAZ (Anais da Academia Brasileira de Ciências, 2020)
Abstract Fleas of Argentina are receiving renewed systematic interest, but the identification of many species associated with small mammals can be problematic. We review the taxonomy of the flea genus Agastopsylla including the re-description of two species and one subspecies, and designate neotype and neallotype for Agastopsylla hirsutior, neotype for Agastopsylla nylota nylota from the “Colección Mamíferos Lillo Anexos” (CMLA), Universidad Nacional de Tucumán, Argentina, and neotype and neallotype for Agastopsylla pearsoni from the Natural History Museum (London, U.K.). Additionally, a key to identification of the species of Agastopsylla and a distribution map of the species of the genus are included.